1992
DOI: 10.1111/j.1365-2672.1992.tb04988.x
|View full text |Cite
|
Sign up to set email alerts
|

M13 DNA fingerprinting, a new tool for classification and identification of Lactobacillus spp.

Abstract: The optimal conditions for the application of M13 DNA fingerprinting to the genus Lactobacillus were determined. Comparative fingerprint analysis of representative strains of Lactobacillus delbrueckii subsp. delbrueckii, Lact. delbrueckii subsp. lactis, Lact. delbrueckii subsp. bulgaricus, Lact. helveticus and Lact. casei permitted the differentiation of species, subspecies and individual strains and the quantitative determination of their genetic relatedness. The results confirm the high specificity of M13 DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Despite the common use of Lact. helveticus in the dairy industry, data on phenotypic and genotypic strain variation reported within the species are limited (Manachini and Parini 1983;Miteva et al 1992;Dykes and von Holy 1994;Drake et al 1996). In a previous paper (Fortina et al 1997) it was shown that several biotechnologically important characteristics can differ greatly among different Lact.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common use of Lact. helveticus in the dairy industry, data on phenotypic and genotypic strain variation reported within the species are limited (Manachini and Parini 1983;Miteva et al 1992;Dykes and von Holy 1994;Drake et al 1996). In a previous paper (Fortina et al 1997) it was shown that several biotechnologically important characteristics can differ greatly among different Lact.…”
Section: Introductionmentioning
confidence: 99%
“…Dot-hybridization analysis was performed by conventional methods with DIG labelled DNA probes using a DIG Labelling and Detection kit (Boehringer). M13 DNA fingerprinting was performed as described by Miteva et al (1992). Ribotyping experiments used the whole rrn operon of E. coli carried by the recombinant plasmid pKK3535 (Brosuis et al 1981).…”
Section: Strain Identificationmentioning
confidence: 99%
“…As M13 is a well known universal polymorphic probe currently used in our laboratory for ¢ngerprint analysis [14,17,18], we compared the pro¢les obtained with pLBL4 and with M13 DNA as probes (Fig. 3).…”
Section: Plbl4 As a Polymorphic Probementioning
confidence: 99%
“…The application of two independent molecular approacheŝ M13 DNA ¢ngerprinting and hybridization with speciesspeci¢c probes^showed that these strains belonged to L. helveticus [14,17]. The plasmid of strain L. helveticus NBIMCC 2727, designated pLBL4, was isolated for further analysis.…”
Section: Isolation and Molecular Characterization Of Plbl4mentioning
confidence: 99%
See 1 more Smart Citation